2022
DOI: 10.1186/s12962-022-00367-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and critical methodological appraisal of community-based falls prevention economic models

Abstract: Background Falls impose significant health and economic burdens on community-dwelling older persons. Decision modelling can inform commissioning of alternative falls prevention strategies. Several methodological challenges arise when modelling public health interventions including community-based falls prevention. This study aims to conduct a systematic review (SR) to: systematically identify community-based falls prevention economic models; synthesise and critically appraise how the models han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Falls impose significant health burdens on community-dwelling older people 19 ) . Thus, fall risk screening is required to identify groups eligible for intervention 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Falls impose significant health burdens on community-dwelling older people 19 ) . Thus, fall risk screening is required to identify groups eligible for intervention 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Provision of adequate nutrition in hospitals is essential to improving patient health outcomes, and plays an important role in reducing rates of malnutrition and subsequent healthcare costs 3 . Nationally and internationally, there are a variety of food service delivery models in use in the acute hospital setting 15 . The delivery model in these settings is largely influenced by the existing food service system infrastructure, resources and cost, but, more recently, patient experience and clinical outcomes have been given some consideration in the development of these models.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 rapid response report with critical appraisal by Young and Farrah evaluated a systematic review of nine non‐randomised studies that compared traditional food service methods with a variety of food service methods including six small meals, room service, individualised menus, meal carts and a la carte 15 . Three of the six studies examining room service found that patients had a significantly higher energy and protein intake.…”
Section: Discussionmentioning
confidence: 99%